Exploration of phosphorescent platinum(II) complexes functionalized by distinct main-group units to search for highly efficient blue emitters applied in organic light-emitting diodes: A theoretical study - Luo, Yafei; Xu, Yanyan; Tian, Li; Zhang, Wenting; Li, Ming; Shen, Wei (Inorganica Chimica Acta, 2015)
Incorporate substituents 1–5 displayed as the above graph into the 4′-position of the phenyl ring of the ppy ligand to study the structure–property relationship of cyclometalated Pt(II) complexes and provide valuable hints for the design of robust blue emitters doped in OLEDs. [Display omitted] •According to the DFT calculations, the complex 4 is promising as deep-blue OLED material.•Emission wavelengths are in the range from 434 to 562nm.•Radiative rate constants dramatically change from 1.00E+04 to 1.22E+05s−1.•Relationship between zero-field splitting and radiative rates were discussed. In this study, five cyclometalated Pt(II) complexes were chosen as research subjects to investigate the effects of main-group moieties on the electronic structure, photophysical properties and radiative deactivation processes of the phosphorescent metal complexes. Density functional theory (DFT)/time-dependent DFT investigation was conducted to gain a better understanding of the properties of these Pt(II) complexes, including the ground and triplet state geometries, absorption spectra and emission wavelength. Moreover, the self-consistent spin–orbit coupling TDDFT (SOC-TDDFT) was used to calculate zero-field splitting (ZFS), radiative rate and radiative lifetime to unveil the radiative deactivation processes for these complexes. The results reveal that the different main-group moieties added on the 4′-position of the phenyl ring in [Pt(ppy)(acac)] could not only dramatically affect molecular and electronic structure, absorption and luminescence properties, but also radiative deactivation processes. And the emission wavelengths of five complexes are in the range from 434 to 562nm. Furthermore, among the studied complexes, the designed complex 4 shows great potential to serve as an efficient deep-blue-light emitter in OLED.